True transformer - Adam, Nur Azura; Muhamad Awang, Rita; Jamian, Syari (Universiti Putra Malaysia Press, 2013)
Insects, like human being, they grow. Insects undergo a series of transformations in their life that includes changes in forms, textures and physical appearances which is called metamorphosis. The journey to adulthood begins with females producing eggs will then hatch becoming the immature stage.